PHP Objects, Patterns, and Practice - Zandstra, Matt (Apress : Imprint: Apress, 2008)
Backed by a tireless development community, PHP has been a model of language evolution over its 10+ year history. Borne from a contract developer's pet project, these days you'll find PHP powering many of the world's largest web sites, including Yahoo!, Digg, EA Games, and Lycos. PHP Objects, Patterns, and Practice, Second Edition shows you how to meld the power of PHP with the sound enterprise development techniques embraced by professional programmers. Going well beyond the basics of object-oriented development, you'll learn about advanced topics such as working with static methods and properties, abstract classes, interfaces, design patterns, exception handling, and more. You'll also be exposed to key tools such as PEAR, CVS, Phing, and phpDocumentor.